(untitled) (Damascus University Journal for engineering sciences, 2021)
One of the reasons leading to decrease the effectiveness and breakdown of the machine operating under dynamic conditions is the dispersion of part of energy directed to an activity in the machine body, or its transformation into another type of non-useful wave. The subject of the research is to conduct an analytical study for one of the reasons that leads to the energy exchange between the longitudinal wave vector and the machine body and its effect on the efficiency and effectiveness of the machine. The conductors metal of longitudinal waves are subjected to stresses of very high values, which leads to longitudinal and transverse deformations in the conductor metal during the passage of the wave and its effect on the clearance separating the carrier and the guide. Therefore, this was clarified by the deducted mathematical equations that show the wave deformations of the conductor metal and the energy transmitted to the machine body that reduces the effectiveness of the machine, its undesirable vibration, and sometimes to its dissociation. In conclusion, the research shows the necessity to take into account the phenomenon accompanying the process of longitudinal wave propagation and its effect on the dimensions of the conductor metal to avoid the negative aspects mentioned previously.